Pengaruh Terapi Musik terhadap Tingkat Hiperaktivitas pada Anak dengan Kondisi Attention Deficit Hyperactivity Disorder (ADHD) - Helmi, Raudhatul Rezkia; Wahyuni, Endang Sri (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common disorder in children, characterized by symptoms of inattention, hyperactivity, and impulsivity that can interfere with individual development. The prevalence of ADHD in Indonesia reaches 26.4%, with a higher rate in boys. Objectives: This study aims to explore the effect of music therapy on the level of hyperactivity of children with ADHD at YPAC Surakarta. Music therapy has been shown to stimulate the brain and reduce symptoms of hyperactivity through increased concentration and impulse control. Through the music intervention program, it is hoped that children can experience a decrease in hyperactive behavior, as well as an increase in social and emotional skills. This research contributes to the understanding of the use of alternative therapies in the treatment of ADHD in Indonesia. Methods: This study uses a quantitative approach with a pre-experimental design, especially one group pretest-posttest design. Samples were taken using purposive sampling techniques based on inclusion criteria. Data analysis was carried out univariate and bivariate, including normality tests and hypothesis tests using paired sample t-tests. This method is designed to provide a clear picture of the impact of music therapy interventions on children with ADHD. Results: The research sample consisted of 17 children, dominated by the category of children with an age range of 5-9 years, totaling 11 people and the majority of whom were male. The results of the paired sample t-test showed that before the music therapy intervention, the average score of the participants was 14.65, while after the intervention, the average decreased to 12.24. The average difference between the two measurements was 2.412. A value of (ρ) less than 0.001 indicates a statistically significant difference. These results indicate that music therapy has a positive effect in reducing the level of hyperactivity in children with ADHD. Conclusion: The application of music therapy can be implemented as an intervention program to reduce hyperactivity levels in children with ADHD. Further research with a larger sample size is also needed, along with the involvement of parents in the therapy to strengthen the intervention outcomes. Keywords: Attention Deficit Hyperactivity Disorder, Hyperactivity, Music Therapy